An MRM‐Based Cytokeratin Marker Assay as a Tool for Cancer Studies: Application to Lung Cancer Pleural Effusions. Issue 2 (7th February 2018) - Perzanowska, Anna; Fatalska, Agnieszka; Wojtas, Grzegorz; Lewandowicz, Andrzej; Michalak, Agata; Krasowski, Grzegorz; Borchers, Christoph H.; Dadlez, Michal; Domanski, Dominik
Abstract : Purpose: The goal of this work was to develop an LC‐MRM assay for the quantitative analysis of a set of established and diagnostically important cytokeratin (CK) markers used in cancer diagnosis, prognosis, and therapy monitoring. Second, the potential of this assay in lung cancer diagnosis through pleural effusion (PE) analysis was examined. Experimental design: A multiplexed MRM assay was developed for 17 CKs and their select caspase‐cleaved fragments. Isotope‐labeled standard peptides were used for high assay specificity and absolute peptide quantitation; with robust standard‐flow LC coupled to a latest‐generation triple‐quadrupole instrument for high sensitivity. The potential clinical applicability was demonstrated by the analysis of 118 PE samples. Results: The MRM assay was evaluated for endogenous detection, linearity, precision, upper and lower limits of quantification, selectivity, reproducibility and peptide stability, and is generally applicable to any epithelial cancer study. A set of 118 patients with known pathologies allowed us to define the range of CK levels in clinical PE samples. Specific CKs were able to differentiate cancer‐related PEs from those caused by benign ailments. In addition, they allowed to differentiate between PEs from subjects with small cell lung cancer versus non‐small cell lung carcinoma, and to further differentiate the latter into its two subtypes, adenocarcinoma and squamous cell carcinoma. Conclusion and clinical relevance: An MRM‐based CK assay for carcinoma studies can differentiate between the three lung cancer histological types using less‐invasive PE sampling providing potential therapy‐guiding information on patients that are inoperable.